Kinetics of Oxidation of Iodide Ion by Ce(IV) - Venkata Nadh, R.; Syama Sundar, B.; Radhakrishnamurti, P.S. (Asian Journal of Chemistry, 2010)
Kinetics of oxidation of iodide ion by Ce(IV) was studied. The reactions are found to be of 1.5 order in case of iodide, first order in Ce(IV) and first order in case of [H+] in the case of uncatalysed reaction. In the case of catalysed reactions both by Ru(III) and Os(VIII) it was noticed that the order with respect to iodide is 1.5, the order with respect to Ce(IV) is one and the dependence on hydrogen ion is found to be one while the reactions are found to be first order in case of both the catalysts Ru(III) and Os(VIII). Plausible mechanisms have been postulated both in the case of uncatalysed and catalysed reactions based upon the experimental observations.